Mexico : 2010 Article IV Consultation; Staff Report and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
This paper reviews the annual progress report on Poverty Reduction Strategy Paper (PRSP) for Republic of Congo. The adoption of the PRSP in March 2008 was followed by adoption of the Operational Action Plan for implementation of the PRSP. The poverty reduction strategy is being implemented in an international economic context marked by a severe economic and financial crisis. The government has also undertaken significant structural administrative reforms with a view to improving political governance.